PENGARUH WATER SPRAY DAUN JAMBU BIJI (PSIDIUM GUAJAVA) PADA PENYEMBUHAN LUKA PERINEUM IBU POST PARTUM - Ika Lestari Sitorus; Farida Umamy; Nanda Puspita (Benih : Journal of Midwifery, 2026)
Perineal wounds are among the most common complications experienced by postpartum mothers and may increase the risk of infection when not managed appropriately. One potential non-pharmacological therapy is guava leaf (Psidium guajava) water spray, which contains flavonoids, tannins, and saponins that contribute to wound healing. This study aimed to analyze the effect of guava leaf water spray on perineal wound healing among postpartum mothers at Pulo Bandring Public Health Center, Asahan Regency, in 2026. A pre-experimental one-group pretest-posttest design was employed. Twenty-five postpartum mothers were recruited using purposive sampling. Wound healing was assessed using the REEDA scale before and after the intervention. Data were analyzed using descriptive statistics and the Wilcoxon Signed Rank Test. The mean REEDA score decreased from 7.80 ± 1.98 before intervention to 2.76 ± 1.20 after intervention. The Wilcoxon test demonstrated a statistically significant difference (Z = −4.451; p = 0.000). Guava leaf water spray was effective in accelerating perineal wound healing among postpartum mothers. This intervention may serve as a safe, practical, and affordable complementary therapy in postpartum care.